No climate justice without sexual and reproductive health, rights and justice (SRHRJ): past, present, and future challenges faced by the Sexual and Reproductive Health and Rights and Climate Justice Coalition - Dijkerman, Sally; McMullen, Heather; Hammond, Natalie, Sexual and Reproductive Health and Rights (SRHR) and Climate Justice Coalition (Frontiers in Reproductive Health, 2025)
The climate crisis jeopardizes human health and is one of the greatest threats to reproductive autonomy and human rights. Witnessing these threats, the Sexual and Reproductive Health and Rights and Climate Justice Coalition was formed in 2021 to advocate on the intersections between climate change and sexual and reproductive health, rights, and justice (SRHRJ). The Coalition's purpose is to leverage intersectional approaches to influence global and national policies, programs, and funding mechanisms to advance climate justice, gender equality, and human rights. Climate justice recognizes the climate crisis as a social, political, and environmental problem and demands fair and equitable solutions. Climate action must be participatory, bottom-up, context-specific, and rooted in locally-led evidence and solutions. Achieving climate justice requires achieving SRHRJ. We reflect on three challenges that led to our founding, and which have shaped the work and priorities of our Coalition: understanding and evidencing the links between climate change and SRHR, pushing back on harmful narratives related to population control and the suggestion that limiting reproduction is a climate solution, and finding just solutions to a complex crisis. Comprehensive SRHR empowers communities to be active participants, leaders, and decision-makers in climate action. Therefore, the Coalition continues to advocate for the importance of multisector, collaborative partnerships, oriented around our shared principles of human rights, intersectionality, bodily autonomy, justice, and inclusive organizing, so that SRHR is integrated into all aspects of climate adaptation.